PEMBERDAYAAN DAN PENGUATAN PENGEMBANGAN USAHA BUMDES MELALUI SISTEM DIGITAL MARKETING KABUPATEN PANGKEP DAN KEPULAUAN - Wagiman S; St. Hatidja Idja; Syarifuddin; Lina Mariana (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2021)
The era of the formation of Village-Owned Enterprises, hereinafter referred to as BUMDesa, is a Legal Entity established by villages and / or with villages to manage businesses, utilize assets, develop investment and productivity, provide services and provide other types of businesses for the greater welfare of the village community, assisting the implementation of government. The purpose of bumdes together has the aim of carrying out economic business activities through a business digitization system, as well as developing investment and economic productivity, and the potential of the village, as well as carrying out fishing activities and village services in general through the supply of fishery facilities and meeting the general needs of the village community, and managing village units, empowerment benefits and digital marketing development of BUMDes. This service method uses documentation and media methods as a means of being carried out in the field and is also a qualitative method is how community service is used to be useful to village communities with conditions according to natural objects and subjects, . The results and discussion of empowerment and business development of bumdes also aim to expand the strategy of developing rural communities. Empowerment and development of village businesses is also carried out through the results of human resource development and development of business units located in pangkep and islands with the development of a digital marketing system as a marketing network, socializing with the regent of Pangkep and islands related to business development and entrepreneurship according to the needs and growth of village businesses, facilities and support for the provision of resources to realize village industrialization through BUMDesa together, efforts in improving the quality of management and strengthening the organization and versification of business business as a business unit through empowerment programs or other activities in the context of strengthening business management and village business units, cooperation or partnerships with fishermen including, 1) Facilitating and strengthening cooperation between BUMDes, 2) facilitating and strengthening cooperation with the business world.